2018
DOI: 10.1111/tpj.13906
|View full text |Cite
|
Sign up to set email alerts
|

Genomic adaptation of flowering‐time genes during the expansion of rice cultivation area

Abstract: The diversification of flowering time in response to natural environments is critical for the spread of crops to diverse geographic regions. In contrast with recent advances in understanding the molecular basis of photoperiodic flowering in rice (Oryza sativa), little is known about how flowering-time diversification is structured within rice subspecies. By analyzing genome sequencing data and a set of 429 chromosome segment substitution lines (CSSLs) originating from 10 diverse rice accessions with wide distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…Previous studies using sequencing information of the Hd1 gene region of 60 landraces [ 27 ] or 429 CSSL materials [ 29 ] illustrated that multiple introgressions and thus dynamic rearrangements occurred around the Hd1 gene. In the present study, we showed that the type 7 mutation occurred in indica rice in insular Southeastern Asia areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using sequencing information of the Hd1 gene region of 60 landraces [ 27 ] or 429 CSSL materials [ 29 ] illustrated that multiple introgressions and thus dynamic rearrangements occurred around the Hd1 gene. In the present study, we showed that the type 7 mutation occurred in indica rice in insular Southeastern Asia areas.…”
Section: Discussionmentioning
confidence: 99%
“…Their studies also revealed that multiple introgressions in the Hd1 gene region had occurred and were important for rice accessions to adapt to different habitats. Furthermore, a set of chromosome segregation substitution lines was used to elucidate the allele variations of common rice flowering-time QTL [ 29 ]. Hd1 was one of the 8 genes under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa) is a typical SD plant whose flowering is promoted under SD conditions, but delayed under LD conditions (Yano et al, 2000). During rice domestication and genetic breeding, rice has dramatically expanded its cultivating areas through modulation of the flowering regulatory pathways (Goretti et al, 2017;Itoh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since domestication, rice cultivation expanded towards different agro-ecological environments by the generation of new cultivars through selection of adapted plants to the new conditions through intense and continuous breeding activities [ 8 ]. One of the barriers that rice overcame to reach temperate regions was the difference in day length that became one of the main determinants of plant adaptation to new areas [ 10 , 11 ]. As a consequence, the genetic distance between cultivars from tropical regions and those cultivated in temperate regions enlarged enough to produce strong reproductive barriers that hinder the genetic flow between tropical and temperate cultivars [ 12 ] and contributing to the constriction of the genetic pool of cultivars and the emergence of different subpopulations.…”
Section: Introductionmentioning
confidence: 99%